Advancing the argument for validity of the Alberta Context Tool with healthcare aides in residential long-term care - Estabrooks, Carole A; Squires, Janet E; Hayduk, Leslie A; Cummings, Greta G; Norton, Peter G (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background Organizational context has the potential to influence the use of new knowledge. However, despite advances in understanding the theoretical base of organizational context, its measurement has not been adequately addressed, limiting our ability to quantify and assess context in healthcare settings and thus, advance development of contextual interventions to improve patient care. We developed the Alberta Context Tool (the ACT) to address this concern. It consists of 58 items representing 10 modifiable contextual concepts. We reported the initial validation of the ACT in 2009. This paper presents the second stage of the psychometric validation of the ACT. Methods We used the Standards for Educational and Psychological Testing to frame our validity assessment. Data from 645 English speaking healthcare aides from 25 urban residential long-term care facilities (nursing homes) in the three Canadian Prairie Provinces were used for this stage of validation. In this stage we focused on: (1) advanced aspects of internal structure (e.g., confirmatory factor analysis) and (2) relations with other variables validity evidence. To assess reliability and validity of scores obtained using the ACT we conducted: Cronbach's alpha, confirmatory factor analysis, analysis of variance, and tests of association. We also assessed the performance of the ACT when individual responses were aggregated to the care unit level, because the instrument was developed to obtain unit-level scores of context. Results Item-total correlations exceeded acceptable standards (> 0.3) for the majority of items (51 of 58). We ran three confirmatory factor models. Model 1 (all ACT items) displayed unacceptable fit overall and for five specific items (1 item on adequate space for resident care in the Organizational Slack-Space ACT concept and 4 items on use of electronic resources in the Structural and Electronic Resources ACT concept). This prompted specification of two additional models. Model 2 used the 7 scaled ACT concepts while Model 3 used the 3 count-based ACT concepts. Both models displayed substantially improved fit in comparison to Model 1. Cronbach's alpha for the 10 ACT concepts ranged from 0.37 to 0.92 with 2 concepts performing below the commonly accepted standard of 0.70. Bivariate associations between the ACT concepts and instrumental research utilization levels (which the ACT should predict) were statistically significant at the 5% level for 8 of the 10 ACT concepts. The majority (8/10) of the ACT concepts also showed a statistically significant trend of increasing mean scores when arrayed across the lowest to the highest levels of instrumental research use. Conclusions The validation process in this study demonstrated additional empirical support for construct validity of the ACT, when completed by healthcare aides in nursing homes. The overall pattern of the data was consistent with the structure hypothesized in the development of the ACT and supports the ACT as an appropriate measure for assessing organizational context in nursing homes. Caution should be applied in using the one space and four electronic resource items that displayed misfit in this study with healthcare aides until further assessments are made.